Analisis Minat Baca Siswa Kelas V Sekolah Dasar Negeri 23 Singkawang - Fazira, Oktaviani; Safrihady, Safrihady; Sumarli, Sumarli (UNIB Press, 2025)
This study aims to describe the reading interest of fifth-grade students at State Elementary School 23 Singkawang and identify the factors influencing their reading interest. The research employs a qualitative approach with a case study design. Data were collected through questionnaires, interviews (with students, teachers, the principal, and the librarian), and documentation. The results indicate that the majority of fifth-grade students have a moderate level of reading interest. Internal factors influencing reading interest include reading ability, reading habits, and motivation. Meanwhile, external factors encompass family environment (parental support), the availability of books and library facilities, and the influence of technology. The study concludes that efforts to enhance reading interest should consider both internal and external factors of students, as well as involve schools, families, and the positive use of technology.